Kajian Etis Tentang Perilaku Pemuda Dalam Ibadah di Jemaat GMIM “Damai Sejahtera” Lahendong Wilayah Tomohon Tiga - Rondonuwu, Claudya Mutrika; Tumiwa, Evi Stans Evlin (UPT Penelitian Fakultas Teologi Universitas Kristen Indonesia Tomohon, 2021)
In this research, the aim is to find out why the GMIM Damai Sejahtera Lahendong Youth did bad things in worship gatherings. Along with the development of science and technology, it also greatly influences the behavior of young people in worship gatherings. The increasingly easy use of the internet has been misused by many people, especially young people. The author sees that bad behavior continues to occur and develops in worship fellowships. Therefore, this research will look at the causes of the youth of GMIM Damai Sejahtera Lahedong doing things that are not good in worship fellowship. With this research, it is hoped that this research can be of interest to pay more attention and provide guidance for the youth. This research uses data collection techniques using qualitative methods including namely: interviews, observation, and literature study.